Education Supervision of Head of School in SMA Negeri I Lembah Seulawah, Aceh Besar Regency - Mustajab Mustajab; Ismail Ismail (BIRCU, 2022)
The implementation of educational supervision at SMA Negeri I Lembah Seulawah Aceh Besar Regency is carried out for the development of student competencies as an effort to build the stages of the learning process, as well as curriculum development through the preparation of learning plans based on the sequence of learning materials. Supervision planning has not gone well in the learning process, principals and teachers plan the implementation of character education by preparing lesson plans and teaching materials. In this case the principal as the leader needs to carry out the function of direction and coordination. The purpose of the study was to analyze the academic supervision of the principal at SMA I Lembah Seulawah Aceh Besar District and to analyze the administrative supervision at SMA I Lembah Seulawah Aceh Besar District using a qualitative approach. Determination of informants is done by purposive sampling and data collection techniques through interview observations and documentation. The results showed that the principal's academic supervision in developing student competencies had not gone well because in the preparation of the learning design the teacher had not been able to make different and varied strategies. Likewise, the development of student competencies, especially teachers, in introducing an interesting phenomenon that has never been recognized by students before has not materialized. The conclusion of the study shows. The importance of educational supervision carried out by school principals for the development of student competencies, including curriculum development by compiling and designing lesson plans in accordance with learning plans based on the sequence of learning materials and selecting learning materials in accordance with the instructional objectives to be achieved. The directive function is also not well coordinated. This condition can get worse if it is not coordinated from planning, implementation, to evaluation.